Policy interventions in renewable energy for sustainable development: is Ghana on the right path to achieve SDG 7? - Ishmael Ackah (African Governance and Development Institute (AGDI), 2016)
Goal 7 of the Sustainable Development Goals seeks to ensure universal access to affordable, reliable and modern energy services and increase substantially the share of renewable energy in the global energy mix by 2030. This target provides an opportunity as well as a challenge to African countries including Ghana. Indeed, the Ghana Energy Commission estimates that Ghana has about 34 potential hydro sites and enjoys about 330 days of sunshine annually. For instance, the three Northern regions, Volta and northern parts of Brong Ahafo have radiation levels with monthly average of between 4.0 and 6.5kWh/m2/day. These hydro and solar resources, coupled with abundant waste, wind potential of about 2000 MW and tidal potential can make Ghana a net exporter of power when the needed investment is provided. This paper examines the policy interventions in renewable energy in Ghana over the past 20 years. It also includes a review of the literature on the relationship between renewable energy investment and sustainable development and provides policy recommendations to fast-track renewable energy technology deployment in Ghana.
Keywords: 330; Renewable Energy; Ghana; Sustainable Development Goals; Energy supply and demand